Definition of riparian buffer zone of the Cauca river between the Balsa and Mediacanoa (2020)
(Eng) The objective of this investigation was to delimit the riparian buffer zone of the Cauca River in the stretch between La Balsa and Mediacanoa. For this, different methodologies has been analyzed and, additionally, the terms of the Preferred Flow Zone (ZFP) and the Dangerous Flood Zone (ZIP) indicated by the Ministry of the Environment and Sustainable Development (MADS) have been considered, in order to determine the riparian buffer zone, as well as i) the location of marginal protection dams as stipulated in Agreement 052 of 2011 of the regional environmental authority of the Valle del Cauca (CVC) and the ecosystem component and ii) ecosystem and geomorphological components. The results show that by applying the ZIP criterion, the area required for the riparian buffer zone is 25,153 hectares, which is equivalent to 84% of the total area of ​​the alluvial plain of the Cauca River between La Balsa and Mediacanoa. Although the proposals evaluated do not meet the ZFP criterion, the water levels of the Cauca River will be reduced to 0.67 m with respect to the current condition. Considering the dynamics and local conditions of the Cauca River in the sector between La Balsa and Mediacanoa, in combination with the results obtained in this study, it is confirmed that the proposed methodologies in Spain (Sustainable Fluvial Territory), The Netherlands and Colombia (MADS) are the most complete to achieve the recovery and conservation of riparian zones. Therefore, a methodology which considers the most relevant aspects of these three methodologies has been created and applied.